Prison gangs for prison life survivability: exploring the reasons for prison gang formation in Kiri-Kiri Maximum security prison - Okwunwanne, Uzoamaka; Chan, Geraldine K.L. (Penerbit Universiti Kebangsaan Malaysia, 2020)
Prison conditions in Kiri-Kiri Maximum prison are harsh due to overcrowding, poor hygiene and outdated prison amenities; however, prisoners survive and endure life in prison because of prison gangs. This study sought to explore the reasons why prisoners form prison gangs and eventually for prison life survivability in Kiri-Kiri Maximum Security Prison. This study made use of a qualitative case study approach to collect data from 34 informants who comprised 2 prison staffs and 32 prison gangs purposively selected. The results from this study discovered that the reasons for prison gang formation were the need to cope, to fulfil the prison authority's needs, for prosocial support and the need for rehabilitation. On the need to cope since the conditions in prison were harsh prison gangs assisted in the maintenance of the prison environment, thus enabling survivability in prison. For fulfilling the prison authority's needs, findings suggest that some of the prison gangs were formed solely to assist the prison authority with menial works. Furthermore, for prosocial support prison gangs provided mutual support to members, thus helping to ease some pains of incarceration. For rehabilitation through vocational workshops, prison gangs are impacted with the life skills needed to survive. The implication of the study is that prison authorities should pay more attention to prison gangs as a way to run the prison effectively.